Teaching Pronunciation at Tertiary Level in Bangladesh - Siddique, Sharmin (Journal of NELTA, 2023)
Pronunciation is the way to give a word an oral or aural shape which is measured as one of the most significant skills of language. For non-native speakers, English pronunciation is considered one of the most tough problems. At the same time, in Bangladesh, teaching English pronunciation is measured one of the most diffi cult parts of ELT. This paper focuses on the challenges confronted by English teachers at the tertiary level to teach pronunciation. This research also tries to focus on the teaching strategies for teaching pronunciation. For collecting data, a survey was conducted and a set of questionnaires was used for teachers. In this survey, 22 English language and literature teachers from various universities took part. Finally, some contextual solutions have been suggested to solve problems of teaching pronunciation in the EFL classroom.